Implementasi Program Parents Course untuk Meningkatkan Pemahaman Orang Tua tentang Auditory Verbal Therapy (AVT) bagi Anak dengan Hambatan Pendengaran di Yayasan Aurica Surabaya - Ana Rafikayati (Universitas Negeri Medan, 2016)
Auditory Verbal Therapy (AVT) is a family based rehabilitation approach of hearing. Families, especially parents become the main persons who takes responsibility in child's language development. This study aimed to describe the implementation parents course program to improve the understanding of Auditory Verbal Therapy (AVT) for parents of children with hearing impairment in Aurica Foundation Surabaya. This research used descriptive qualitative research. Research’s subject in this research are the AVT therapists of Aurica foundation, audiologists and parents of children with hearing impairment. Data collection used interviews, observation and documentation techniques. Data analysis used flow analysis of Miles Huberman covering steps of data reduction, data display and verification. The results of this research is known that the implementation of parents course program course to improve the understanding of AVT for parents of children with hearing impairment in Aurica Foundation Surabaya is covering the planning, implementation and evaluation. In planning stage, the trainer analyzed needs of the knowledge AVT. Parents course consists of 4 stages: stage I, II, III, and IV. The program starts from the easy material to complex. The implementation of the parents course program is done in 4 phases. The technique used during training are presentation, discussions and demonstrations. Program evaluation of parents course done by a comparative pre-test and post-test design.